Sustained censorship in EG (2026-04) (Egypt) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Egypt. Data sourced from OONI.
Censorship Incident ID: EG-2026-0422. Severity: critical. Confidence: 80%